A PERSPECTIVE ON THE DICHOTOMY OF ACQUISITION OF PARENTAL RESPONSIBILITIES AND RIGHTS BY FATHERS IN TERMS OF THE CHILDREN’S ACT AND CUSTOMARY LAW - Gugulethu Nkosi (Obiter, 2018)
South Africa’s legal system is pluralist in nature. It is embedded in two components, namely, customary law and the common law, which converge to form one national legal system through legislation and case law. However, the distinct development of these two components of the legal system has a significant impact on how their respective frameworks are perceived and subsequently applied in given cases. Traditional African family systems were regulated under the “banner” of customary law, but the validity of the system was ultimately decided in terms of the common law, subject to the repugnancy clause. The repugnancy clause was introduced during the colonial era and was used as a measure discarding certain indigenous African values as contrary to public policy and natural justice (see Juma “From ‘Repugnancy to Bill of Rights’: African Customary Law and Human Rights in Lesotho and South Africa” 2007 21 Speculum Juris 88). Hence, the common law was generally preferred to customary law. This state of affairs influenced the manner in which the two components of the legal system developed, entrenched an outlook of a subservient position towards African customary law particularly in relation to parental responsibilities and rights as asserted below. This position, in turn, rattles the traditional family value system of the indigenous African people.This state of affairs persists regardless of the fact that in the new constitutional dispensation, customary law has been afforded legitimate recognition. Section 211 (3) of the Constitution provides that the courts must apply customary law when that law is applicable, subject to the Constitution and any legislation that specifically deals with customary law. Furthermore, section 39(3) recognises the rights and freedoms “that are recognised or conferred by common law, customary law or legislation, to the extent that they are consistent with the Bill of Rights”.The official recognition of customary law necessitated that the application of the customary law and the common law within the same legal system be harmonised. Issues pertinent to the harmonisation of the common law and customary law were discussed in the South African Law Commission Report of 1999 (South African Law Commission Report “Harmonisation of the Common Law and the Indigenous Law: Report on Conflicts of Laws” Project 90 of 1999). One of the issues raised in the report was how to determine when the customary law is applicable (Himonga and Bosch “The Application of African Customary Law under the Constitution of South Africa: Problems Solved or Just Beginning? 2000 117 South African LJ 314). It was found that generally, the judiciary exercises its own discretion to decide when to apply the customary law (South African Law Commission Report of 1999). A constant challenge that the judiciary faces is to ascertain the customary law position in a given case. This exercise generally requires probing of both the “official” and “living” versions of the customary law. Needless to say, an investigation of this nature is complex. Normally the traditional customary law position, that is, the living customary law of the pre-colonial is considered in light of its significance in the contemporary society. The diverse plethora of customs and cultures has further compounded the process of ascertaining a customary law position of the various indigenous African groups. Finally, it is essential that the judiciary consider the manner in which a group interprets and applies a particular custom. Due to the said complexities that prevail when attempting to ascertain the African customary law position, the attitude, then is generally to adopt the apparent African customary law position.In light of the said entrenched tensions between customary law and common law in terms of application, this note seeks to explore the dichotomy of the acquisition of parental responsibilities and rights as portrayed in legislation and in terms of customary law. Specific reference will be made to the legal position of unmarried fathers in this regard. This note investigates how parental responsibilities and rights are acquired as provided for in legislation. It further examines whether, in terms of customary law, unmarried fathers can acquire parental responsibilities and rights as stipulated in the legislation.